(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the phytochemical composition of hydroalcoholic extracts from the seeds of Persea americana (avocado) and evaluate the larvicidal activity against Aedes aegypti. The extracts were obtained by maceration in a 70% PA ethanol extractant solvent in 1:4/1:6/1:8 hydromodules (7 days), with subsequent concentration in a rotaevaporator. The larvicidal activity was performed by the method recommended by the WHO Lethal Concentration 50% against Aedes aegypti larvae with statistics by the Probit method. Toxicity to non-target organisms was verified by the Artemia salina test. Activity was observed against Aedes aegypti larvae with LC50 ranging from 181.72-401.96 mg L-1 with a 95% confidence interval. Finally, it states that the extract of P. americana has potential for larvicidal activity and does not present toxicity to target organisms, showing itself to be a sustainable alternative for the control and combat of Aedes aegypti larvae.